Lay-Off Seniority Clause and Management Rights (Relations industrielles / Industrial Relations, 1959)
SummaryBy the majority, where there is no specification on the procedure to be followed in cases of lay-offing employees with equal seniority the employee with the greater number of days of service should have the preference.